Asuhan Keperawatan Keluarga Pada Keluarga Dengan Scabies Di Wilayah Kerja Puskesmas Naras Kota Pariaman 2026 - Giska Dwi Aprilianda; Armaita Armaita; Hasmita Hasmita; Sandra Dewi (CV. ITTC INDONESIA, 2026)
According to the World Health Organization (2023), the incidence of scabies in the world reaches more than 200 million people at any given time with more than 400 million cumulative cases annually. The number of cases in Indonesia is estimated at around 1.8 million cases in 2022. Based on data in West Sumatra Province in 2024 there were 69,659 cases of infectious skin diseases. In Pariaman City in 2025 there were 2,400 cases of scabies. At Naras Community Health Center in 2025 there were 65 cases of scabies. The purpose of this study is to understand and apply family nursing care to patients with scabies. Scabies is a skin disease caused by the small mite Sarcoptes scabiei that lives in the skin of the sufferer. This study used a case study method conducted at Naras Community Health Center from March 8 to March 13, 2026. The results of the study on An. I showed three nursing diagnoses, namely impaired skin integrity, disturbed sleep patterns, and knowledge deficit. The interventions provided included scabies education, skin integrity care, the use of aloe vera and coconut oil as supportive therapy, the implementation of clean and healthy living behaviors (PHBS), and prevention of transmission within the family. An. I's family was able to implement the given implementation. Based on the case study conducted, it can be concluded that the implementation of nursing care for 6 days found 3 well-controlled nursing problems. The results of this study are expected to be a reference for authors, educational institutions, families, and health workers in improving the understanding and quality of family nursing care for patients with scabies. Follow-up home visits are recommended to monitor the consistency of PHBS implementation and prevent reinfection.